If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(331/6)-7=b
We move all terms to the left:
(331/6)-7-(b)=0
We add all the numbers together, and all the variables
-b-7+(+331/6)=0
We add all the numbers together, and all the variables
-1b-7+(+331/6)=0
We get rid of parentheses
-1b-7+331/6=0
We multiply all the terms by the denominator
-1b*6+331-7*6=0
We add all the numbers together, and all the variables
-1b*6+289=0
Wy multiply elements
-6b+289=0
We move all terms containing b to the left, all other terms to the right
-6b=-289
b=-289/-6
b=48+1/6
| k-15=9 | | 2+6x=1- | | 18+8v=17v | | w-5.12=6.69 | | v+1.6=6.24 | | 6(3+X-5)-9a=0 | | 88=1/2(a)(11) | | 3/4m+2/3m=4+1/6m | | 25x+17=1360 | | a=8/4+3 | | H/10=-22x | | 962=u+463 | | t-608=158 | | 36a−=165 | | 3x+5=-8x-1 | | y+304=593 | | (17+x)4=756 | | h-2=25 | | t+7=91 | | 31=j-40 | | x+(0.5x)=21 | | n-10=47 | | (52-46)/(x+1)=6 | | p-56=32 | | 1,000,000=3(5)^x | | 15-20x=3-x | | c=–3 | | c=–3= | | 1=10x2+9x | | 75-x=12/100 | | 4.5=x-4.23 | | 5b+6=74.5 |